Imidazole‐Grafted Nanogels for the Fabrication of Organic–Inorganic Protein Hybrids. (11th July 2018) - Rodriguez‐Abetxuko, Andoni; Morant‐Miñana, Maria Carmen; López‐Gallego, Fernando; Yate, Luis; Seifert, Andreas; Knez, Mato; Beloqui, Ana
Abstract: Here, a platform for the development of highly responsive organic–inorganic enzyme hybrids is provided. The approach entails a first step of protein engineering, in which individual enzymes are armored with a porous nanogel decorated with imidazole motifs. In a second step, by mimicking the biomineralization mechanism, the assembly of the imidazole nanogels with CuSO4 and phosphate salts is triggered. A full characterization of the new composites reveals the first reported example in which the assembly mechanism is triggered by the sum of Cu(II)–imidazole interaction and Cu3 (PO4 )2 inorganic salt formation. It is demonstrated that the organic component of the hybrids, namely the imidazole‐modified polyacrylamide hydrogel, provides a favorable spatial distribution for the enzyme. This results in enhanced conversion rates, robustness of the composite at low pH values, and a remarkable thermal stability at 65 °C, exhibiting 400% of the activity of the mineralized enzyme lacking the organic constituent. Importantly, unlike in previous works, the protocol applies to the use of a broad range of transition metal cations (including mono‐, di‐, and trivalent cations) to trigger the mineralization mechanism, which eventually broadens the chemical and structural diversity of organic–inorganic protein hybrids. Abstract : A new platform for the assembly of organic–inorganic protein hybrids based on imidazole‐grafted enzyme nanogels is presented. The ability of the imidazole nanogels to mimic the biomineralization mechanism with a broad number of metallic salts allows the fabrication of protein hybrids on demand. Particularly, the use of enzyme nanogels leads to highly active, robust, and thermostable heterogeneous catalysts.